SUNTINGAN DAN ANALISIS ISI TEKS AKSARA ULU DALAM KOLEKSI PETI 91/E6 - Nur Anida; Nyimas Umi Kalsum; Otoman Otoman (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2021)
This thesis entitled “Editing.Teks.dan.Analisis.Isi.Teks in PNRI Collection Peti 91/E6” is a Malay script written in Ulu script using regional dialect. The essence of the formulation of the problem in this thesis: (1) How is the philological study of the Ulu Script in the Collection of PNRI Peti No. 91/E6 (2) What is the content of the Ulu script in the PNRI Collection Peti No. 91/E6. This study uses a qualitative research method carried out by direct observation of primary data obtained from the PNRI Building on the 9th floor on the Nusantara Manuscripts Collection Service by documenting the discovery of data contained in the Book of the Archipelago Manuscripts Master Catalog Volume 4 published by the Foundation. Indonesia Torch 1998 on page 385, section of the Malay Manuscript Catalog. Then in the book Supporting the Cultural Heritage of the South Sumatra Ulu Manuscript published by the South Sumatra Provincial Government, the Culture and Tourism Office on page 22. In the research paper, the researcher uses a philological approach, namely with Manuscript Inventory, Manuscript Description, Manuscript Copying, Text Editing, and Text Analysis on Manuscripts. The collection manuscript with Case Number 91/E6 is a single manuscript made of brown bamboo, totaling 20 blades, in a legible condition. The text of the manuscript contains a folklore about a beetle looking for a flower bud. The idea presented in this manuscript is a law regarding the requirements for finding a mate through the intermediary of the Prophet and Priyayi. The teaching is conveyed by means of poetry as if it is sung in the reading. This proves that ancient cultural life had religious teachings.